Avaliação da educação superior na Universidade Estadual da Paraíba: análise dos cursos avaliados em 2019 - Timbó, Bruno Henrique Oliveira (2020)
The present research had as general objective to analyze the evaluation process of the face-to-face undergraduate courses at the State University of Paraíba (UEPB), through the reports elaborated by the on-site verification commissions designated through the State Education Council of Paraíba (CEE/PB). This dissertation has a qualitative approach of an applied nature; its objectives consist of an exploratory and descriptive scope; and used as a procedure the bibliographic and documentary analysis. The basis of the research was developed by means of a survey of the legal norms that support higher education in Brazil, highlighting the specificities that comprise the regulatory bodies of Higher Education Institutions (HEIs), as well as theoretically based on the Authors dealing with the theme the evaluation of higher education José Dias Sobrinho, Dilvo Ivo Ristoff, Robert Verhine, among others. We adopted the SWOT analysis as a resource to contribute to the identification of the strengths, weaknesses, opportunities and threats that had a positive and negative impact on the quality of the evaluation process of the on-campus undergraduate courses of the researched HEI. In this perspective, it was demonstrated a good performance of the courses evaluated in the dimensions of pedagogical didactic organization and faculty and tutorial. However, the infrastructure dimension proved to be a weakness presented by the courses and by the UEPB as a whole. As a result, it was found that, in relation to face-to-face undergraduate courses, although they had a favorable assessment by the on-site verification commissions, it is necessary to create permanent mechanisms for self-assessment and updating of the Pedagogical Course Projects (PPCs) ) according to current legislation, even though the CEE/PB fully adopts the Assessment Instrument for On-campus and Distance Graduation Courses of the National Higher Education Assessment System (SINAES) as a way to better identify the particularities of each course and institution evaluated. Finally, suggestions from this research are that the UEPB's administrative management eliminates the numerous existing accessibility barriers, as well as establishes better infrastructure conditions and, through the reestablishment of the financial order, acts to reduce the number of substitute teachers and comply with the Positions, Careers and Compensation Plan (PCCR) for the categories of teachers and administrative technicians.